Beyond the Ebook: Digital Ecologies and the Future of the Author-Publisher Relationship, and Bibliotek: A Novel - McLaughlan, Paul James (Curtin University, 2013)
This thesis examines changes in book publishing arising from digital distribution and textual ecology, and how these affect the traditional publisher-author relationship. It considers how the inclusion of fan writers into the industry may help publishing develop in positive ways. The critical exegesis develops a model for a transformative, sharing readership to work with the industry, helping to revitalise the form; while the creative component, science fiction novel, Bibliotek, extrapolates how this model could function.